Interarm Difference in Blood Pressure: Reproducibility and Association with Peripheral Vascular Disease - Jesper Mehlsen; Niels Wiinberg (International Journal of Vascular Medicine)
The present study aimed at examining the interarm difference in blood pressure and its use as an indicator of peripheral arterial disease (PAD). Data were included from consecutive patients referred from their general practitioner to our vascular laboratory for possible PAD aged 50 years or older without known cardiac disease, renal disease, or diabetes mellitus. 824 patients (453 women) with mean age of 72 years (range: 50–101) were included. 491 patients had a diagnosis of hypertension and peripheral arterial disease (PAD) was present in 386 patients. Systolic blood pressure was 143 ± 24 mmHg and 142 ± 24 mmHg on the right and left arm, respectively (P=0.015). The interarm difference was greater in patients with hypertension (P=0.002) and PAD (P<0.0005). 443 patients were measured on two separate occasions and the interarm difference for systolic blood pressure was reproducible for differences >20 mmHg. This study confirmed the presence of a systematic but clinically insignificant difference in systolic blood pressure between arms. The interarm difference was larger in hypertension and PAD. Consistent lateralisation is present for differences ≥20 mmHg and an interarm difference >25 mmHg is a reliable indicator of PAD in the legs.